2019
DOI: 10.1080/09546634.2018.1544405
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on a PRP-like cosmetic, biomimetic peptides based, for the treatment of alopecia areata

Abstract: Background: Alopecia areata (AA) is a non-scarring auto-immune hair disorder. Recent researches explained the role of growth factors (GFs) in hair follicle cycling. The main reservoir of GFs are alpha-granules of platelets and novel procedures have been implemented aimed at collecting platelet-rich plasma (PRP). PRP has been safely implemented in many medical applications and has also been successfully used as alternative cell-based therapy for the treatment of hair growth disorders, among which also AA. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
2
13
0
Order By: Relevance
“…Of the 160 subjects enrolled in the study, a significant improvement in hair regrowth was recorded in the majority of the 80 subjects treated with the active product. These results are in line with those from our previous studies in which we demonstrated the efficacy of a pool of peptides derived by biotechnology that mimic platelet growth factors in AA [16] and AGA [17]. These peptides include copper tripeptide-1, oligopeptide-20, acetyl decapeptide-3 and octapeptide-2.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of the 160 subjects enrolled in the study, a significant improvement in hair regrowth was recorded in the majority of the 80 subjects treated with the active product. These results are in line with those from our previous studies in which we demonstrated the efficacy of a pool of peptides derived by biotechnology that mimic platelet growth factors in AA [16] and AGA [17]. These peptides include copper tripeptide-1, oligopeptide-20, acetyl decapeptide-3 and octapeptide-2.…”
Section: Discussionsupporting
confidence: 91%
“…Grading of the overall improvement in the subjects in group 1 and 2, respectively, is reported in Table 5. In group 1, 47.50% of subjects achieved a complete regression (A5) and, in line with results from previous studies [16], 13.75% achieved a partial regression (A3); only 6.25% of subjects in group 1 reported no response at all ( Table 5). In contrast, only 5% of the subjects in group 2 reported a complete regression ( Table 5).…”
Section: Inclusion Criteria Exclusion Criteriasupporting
confidence: 90%
See 1 more Smart Citation
“…Comorbidities information is necessary to confirm the evidence reported in this study. Moreover, information about androgenic alopecia incidence before the start of the chemotherapy in our population is lacking; this can interfere with the obtained results, thus further studies including data about alopecia and its genetic predisposition are warranted (Rinaldi et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…For IUA therapy, E 2 is typically administered as an oral or systemic formulation, which presents restricted clinical application due to its limited half-life in vivo, and is commonly employed combined with other bioactive substances [ 12 , 13 ]. PRP is an autologous concentration of platelets that has been used as a new therapeutic option for different pathologies, such as musculoskeletal diseases [ 14 , 15 , 16 ], cosmetic medicine [ 17 , 18 , 19 ], and cardiology [ 20 , 21 ]. PRP releases growth factors and cytokines, such as vascular endothelial growth factor (VEGF) [ 22 ], platelet-derived growth factor, epidermal growth factor (EGF) [ 23 ], transforming growth factor (TGF) [ 24 ], and other cytokines that modulate angiogenesis [ 25 ], affect recruitment proliferation [ 11 ] and stimulate cell differentiation and growth [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%